PENGARUH PELAYANAN, SUASANA TOKO DAN LOKASI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MODERASI PADA 11’ (SEBELAS) VAPESTORE DI TENGGARONG - AWALUDIN; Ilham; Noorhya Akhmar Ramadhan Putri, Eva (I-Con Media, 2025)
The existence of smoking behavior as part of a lifestyle and necessity, as well as seeing the dangers of smoking which are quite high, has led to the emergence of technological innovation in terms of smoking with electronic cigarette products or electric vaporizers which are usually called vapes. . The aim of this research is to determine the role of customer satisfaction as a moderating variable whether it is able to strengthen the influence of service, shop atmosphere and location on customer loyalty. The population in this study were 11 customers in Tenggarong. The sample in this study was 90 people who had made purchases at 11 Tenggarong. Sampling used non-probability sampling techniques and data analysis tools using Structural Equation Modeling (SEM) using Smart PLS version 4 software. The results of the research show that (1) Service has no effect on Customer Loyalty (2) Store Atmosphere has no effect on Customer Loyalty (2) Store atmosphere has no effect on customer loyalty (3) Location has no effect on customer loyalty (4) Customer satisfaction has no effect on customer loyalty (5) Customer satisfaction does not moderate service on customer loyalty (6) Customer satisfaction does not moderate store atmosphere on customer loyalty (7) Customer Satisfaction does not moderate Location on Customer Loyalty.